Analisis Kesulitan Keterampilan Berbicara Bahasa Jawa Kelas IIa Sekolah Dasar - Setyowati, Eny; Nuvitalia, Duwi; Purnamasari, Veryliana; Kurnia, Evivalen Arnis (Education Journal : Journal Educational Research and Development, 2024)
Speaking skills are the ability to express an idea through thoughts or feelings. The use of Javanese to communicate for class IIA students at Bukit Aksara Elementary School is still low, this is because students rarely speak Javanese and the environment is unfamiliar, resulting in a lack of enthusiasm for Javanese language subjects. The research was carried out with the aim of describing difficulties in Javanese speaking skills for class IIA students and the factors causing them. The research conducted was descriptive qualitative.Using trialuation techniques to collect data consisting of observations, teacher and student interviews. The research results show that 70% of students do not speak Javanese fluently, this is due to limited vocabulary, inaccurate pronunciation of verbal phonemes and consonants. The causes of these difficulties include factors (1) Language including language use, vocabulary and habits at home and at school, (2) non-language, the role of the teacher, home environment, school environment and communication between families.